Effect of Monosaccharides Including Rare Sugars on the Bilayer Phase Behavior of Dimyristoylphosphatidylcholine - Nobutake Tamai; Mei Kamiya; Nono Kiriyama; Masaki Goto; Kazuhiro Fukada; Hitoshi Matsuki (Membranes)
We observed bilayer phase transitions of dimyristoylphosphatidylcholine (DMPC) in aqueous solutions of four kinds of monosaccharides, namely, D-glucose, D-fructose, D-allose and D-psicose, using differential scanning calorimetry (DSC). D-allose (C3-epimer of D-glucose) and D-psicose (C3-epimer of D-fructose) are rare sugars. We performed DSC measurements using two types of sugar-containing sample dispersions of the DMPC vesicles: one is a normal sample dispersion with no concentration asymmetry between the inside and outside of the vesicles and the other is an unusual sample dispersion with a concentration asymmetry. DSC measurements using normal sample dispersions with different sugar concentrations revealed that the temperatures and transition enthalpies of the pre- and main transition of the DMPC bilayer membrane did not significantly depend on the sugar concentration for all monosaccharides. DSC measurements using the unusual sample dispersions demonstrated that the concentration asymmetry caused the splitting of the endothermic peak of the main transition similarly irrespective of the sort of monosaccharides present. From all these DSC results, we conclude that (i) most monosaccharide molecules exist in the bulk water phase, (ii) no specific interaction depending on the molecular structure of each monosaccharide directly occurs between the DMPC and each monosaccharide molecule, and (iii) almost all the effects of the monosaccharides observed in this study are understandable as the general colligative properties of solutions.